PENGARUH GENDER, ETHICAL SENSITIVITY, LOCUS OF CONTROL, DAN PEMAHAMAN KODE ETIK PROFESI AKUNTAN TERHADAP PERILAKU ETIS MAHASISWA AKUNTANSI UNIVERSITAS SYIAH KUALA - Dara Yovita, Cut Safira; Rahmawaty, Rahmawaty (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
The purpose of this research is to examine some factors that may effect ethical behavior of accounting students of Syiah Kuala University. There are four variables hypothesized affect ethical behavior which are gender, ethical sensitivity, locus of control and comprehensif of accountant profession ethical code.The respondents are the accounting students of Syiah Kuala University who have attended courses in Auditing. The samples are collected using simple random sampling method and resulted 74 students become the final samples. This research uses multiple regression linear analysis.The result of this research show that simultaneous of gender, ethical sensitivity, locus of control and comprehensif of accountant profession ethical code have effect on ethical behavior of accounting students of Syiah Kuala University. Partially the research shows that all variables are significantly effected on ethical behavior of accounting students of Syiah Kuala University.Keywords: Ethical behavior, gender, ethical sensitivity, locus of control, comprehensif of accountant profession ethical code